Projecting the cost of introducing typhoid conjugate vaccine (TCV) in the national immunization program in Malawi using a standardized costing framework. Issue 12 (15th March 2022) - Debellut, Frédéric; Mkisi, Rouden; Masoo, Vincent; Chisema, Mike; Mwagomba, Dennis; Mtenje, Mphatso; Limani, Fumbani; Mategula, Donnie; Zimba, Boston; Pecenka, Clint
Abstract: Background: There is a substantial typhoid burden in sub-Saharan Africa, and TCV has been introduced in two African countries to date. Decision-makers in Malawi decided to introduce TCV and applied for financial support from Gavi, the Vaccine Alliance in 2020. The current plan is to introduce TCV as part of the national immunization program in late 2022. The introduction will include a nationwide campaign targeting all children aged 9 months to 15 years. Following the campaign, TCV will be provided through routine immunization at 9 months. This study aims to estimate the cost of TCV introduction and recurrent delivery as part of the national immunization program. Methods: This costing analysis is conducted from the government's perspective and focuses on projecting the incremental cost of TCV introduction and delivery for Malawi's existing immunization program before vaccine introduction. The study uses a costing tool developed by Levin & Morgan through a partnership between the International Vaccine Institute and the World Health Organization and leverages primary and secondary data collected through key informant interviews with representatives of the Malawi Expanded Programme on Immunization team at various levels. Results: The total financial and economic costs of TCV introduction over three years in Malawi are projected to be US$8.5 million and US$29.8 million, respectively. More than two-thirds of the total cost is made up of recurrent costs. Major cost drivers include the procurement of vaccines and injection supplies and service delivery costs. Without vaccine cost, we estimate the cost per child immunized to be substantially lower than US$1. Discussion: Findings from this analysis may be used to assess the economic implications of introducing TCV in Malawi. Major cost drivers highlighted by the analysis may also inform decision-makers in the region as they assess the value and feasibility of TCV introduction in their national immunization program.